DETERMINATION OF THE DEGREE OF RISK OF EMERGENCIES WITH THE USE OF FUZZY LOGIC - Ulianovska, Yuliia V.; Yakovenko, Vadim О.; Mala, Yuliia A.; Yakovenko, Tetiana Y.; Avilova, Valeriia O. (Systems and Technologies, 2022)
Summary. The study analyzes existing methods for determining the risk of accidents. The authors propose a modification of the method of assessing the risks of dangerous situations at work. The method is based on the theory of fuzzy sets and the concept of linguistic variable. This approach makes it possible to adapt it to any production by changing the criteria and names of input variables. Fuzzy Logic Toolbox, a MATLAB extension package, was used to model the system. The paper concludes that determining the degree of risk of any production makes it possible to form an appropriate to the degree of risk set of actions aimed at preventing emergencies.